Tindak Pidana Pencurian Dengan Kekerasan - Zulfikar Zulfikar; Khaerul Mannan; Phireri Phireri (Jurnal Litigasi Amsir, 2023)
This study aims to find out the application of material criminal law by judges in the case of the Barru PN decision number 96/Pid.B/2021/PN.Barru and to know the judge's material legal considerations in the Barru PN decision case number 96/Pid.B/2021/PN .Barru. The research method used in this paper is normative research. The results of the research show that the Judge in deciding case Number 96/Pid.B/2021/PN.Barru was right and in accordance with the provisions of material and formal criminal law so that the decision was legally valid. In connection with all the elements legally and convincingly fulfilled according to law, it can be concluded that the elements of the crime of theft with violence have been fulfilled. The judge's considerations in imposing criminal sanctions on the perpetrators of the crime of theft with violence in decision number: 96/Pid.B/2021/PN.Barru namely by seeing that all the elements of the article in the Indictment are fulfilled in the form of a single indictment Article 365 paragraph 1 of the Criminal Code which is based on 2 (two) pieces of evidence plus the conviction of the judge. In addition, the judge in imposing criminal sanctions must consider mitigating and aggravating circumstances for the defendant